Esketamine Combined with Dexmedetomidine to reduce Visceral Pain During elective Cesarean Section Under Combined Spinal-Epidural Anesthesia: A double-Blind Randomized Controlled Study - Yang JR; Li YY; Ran TJ; Lin XY; Xu JY; Zhou SL; Huang PJ (Dove Medical Press, 2024)
Ji-Rong Yang,1 Ying-Yuan Li,2 Tao-Jia Ran,1 Xiao-Yu Lin,1 Jin-Yan Xu,1 Shao-Li Zhou,1 Pin-Jie Huang1 1Department of Anesthesiology, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong Province, People's Republic of China; 2Department of Anesthesiology, Huadu District People's Hospital, Guangzhou, Guangdong Province, People's Republic of ChinaCorrespondence: Pin-Jie Huang; Shao-Li Zhou, The Third Affiliated Hospital of Sun Yat-sen University, No. 600 Tianhe Road, Guangzhou, Guangdong Province, People's Republic of China, Email hpjie@126.com; 13610272308@139.comPurpose: We aimed to evaluate the effect of intravenous esketamine combined with dexmedetomidine as supplemental analgesia in reducing intraoperative visceral pain during elective cesarean section under combined spinal-epidural anesthesia (CSEA).Patients and Methods: A total of 269 parturients scheduled for elective cesarean section under CSEA between May 2023 and August 2023 were assessed. The parturients were randomly allocated to receiving either intravenous infusion of 0.3-mg/kg esketamine combined with 0.5-μg/kg dexmedetomidine (group ED, n=76), 0.5-μg/kg dexmedetomidine (group D, n=76), or normal saline (group C, n=76) after umbilical cord clamping. The primary outcome was intraoperative visceral pain. Secondary outcomes included the visual analog scale (VAS) score for pain evaluation and other intraoperative complications.Results: The incidence of visceral pain was lower in group ED [9 (12.7%)] than in group D [32 (43.8%)] and group C [36 (48.6%), P < 0.0001]. The VAS score was also lower in group ED when exploring abdominal cavity [0 (0), P < 0.0001] and suturing the muscle layer [0 (0), P =0.036]. The mean arterial pressure was higher in group D [83 (9) mmHg] and group ED [81 (11) mmHg] than in group C [75 (10) mmHg, P < 0.0001] after solution infusion. The heart rate after infusion of the solution was lower in group D [80 (12) bpm] than in group C [86 (14) bpm] and group ED [85 (12) bpm, P = 0.016]. The incidence of transient neurologic or mental symptoms was higher in group ED compared to group C and group D (76.1% vs 18.9% vs 23.3%, P< 0.0001).Conclusion: During cesarean section, 0.3-mg/kg esketamine combined with 0.5-μg/kg dexmedetomidine can alleviate visceral traction pain and provide stable hemodynamics. Parturients receiving this regimen may experience transient neurologic or mental symptoms that can spontaneously resolve at the end of the surgery.Plain language summary: Some parturients endure experience indescribable pain and discomfort during fetal delivery. Esketamine combined with dexmedetomidine can alleviate this pain during cesarean section under combined spinal-epidural anesthesia. However, after intravenous injection of esketamine and dexmedetomidine, the parturients may experience nightmares, dizziness, hallucinations, and drowsiness, etc.Keywords: cesarean section, dexmedetomidine, esketamine, CSEA, visceral pain